ROMANTISME DALAM ISLAM (KRITIK TERHADAP REPRESENTASI CINTA DALAM FILM MERINDU CAHAYA DE AMSTEL) - Putri Agnijar; Ganjar Eka Subakti (Rumah Jurnal STAIN Majene, 2025)
This study aims to analyze the representation of love in the film “Merindu Cahaya de Amstel” from an Islamic perspective. Using a descriptive qualitative approach and narrative analysis, this study examines the film's script, dialogue, and visual elements to evaluate their consistency with Islamic teachings on love. Data was collected through direct observation of the film and content analysis, then compared with Islamic perspectives found in the Qur'an, Hadith, and related academic literature. The results of the study show that the film depicts love as a journey that includes spiritual and emotional struggles, and features themes of communication and personal growth. However, there are several scenes that show romantic interactions that do not comply with Islamic boundaries, such as physical contact without marriage. The study also found the influence of popular culture in the film's narrative, which can affect Muslim audiences' perceptions of love. The research concludes that while the film offers valuable insights into the complexity of love in Islam, there are elements that require criticism. Recommendations for further research include urging filmmakers to be more sensitive in representing Islamic values of love and examining other films with similar themes.